Events management an introduction - Bladen, Charles; Abson, Emma; Kennell, James; Wilde, Nick (London New York Routledge, Taylor & Francis Group, 2023)
"Contemporary events management is a diverse and challenging field. This introductory textbook fully explores the multidisciplinary nature of events management and provides the student with all the practical skills and professional knowledge they need to succeed in the events industry. Written by a team of authors with many years' experience of working in the events industry, Events Management: An Introduction is the essential course text for any events management programme"--
Includes bibliographical references and index.
Keywords: Special events -- Management